Rapid Land Assessment for Salt Farming Development in the Coastal Area of the Special Region of Yogyakarta, Indonesia - Mukhamad N. Malawani; Muh Aris Marfai; Aldhila G. H. Yoga; Tiara Handayani; Ahmad Cahyadi; Mohammad Isnaini Sadali; Mohamad Zaki Mahasin; Hendratmoro; Suadi; Maryadi Budi Wiyono (ASEAN Journal on Science and Technology for Development, 2021)
The government of Indonesia has faced several challenges to its goal of achieving salt self-sufficiency, necessitating the formulation and implementation of strategic steps to increase salt production. Among its islands, Java has a great deal of potential for salt production, as does the Special Region of Yogyakarta, where the government has initiated salt farming development as part of its coastal community empowerment program. This study aimed to (1) evaluate the land suitability of existing salt farms and (2) identify potential sites and make a productivity estimation of salt farms in the Special Region of Yogyakarta, with the broad objective of demonstrating a rapid land assessment for salt farming development using the combination GIS and field survey. The approach was carried out in three phases; i.e., the analyses of land availability, land characteristics, and land recommendations. On-screen digitizing using GIS was applied to identify land availability through several data sources (satellite imagery and a land-use map from the Indonesian topographic map). This process led to the discovery of 19 sites. Land characteristics and land recommendations analysis were carried out in those sites, resulting in multiple land suitability classes, mostly in the S2 class (moderately suitable). Several impediment factors, such as wind, material texture, and temperature, were also identified, along with other obstacles including high tide and tsunami exposure. In terms of supporting the Indonesian salt self-sufficiency program, these results are significant, with salt productivity estimations of the potential sites meeting the target set by the Ministry of Marine Affairs and Fisheries of Indonesia.